1996
DOI: 10.1172/jci119029
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-mediated 15-lipoxygenase expression protects against atherosclerosis development.

Abstract: Oxidative modification of LDL increases its atherogenicity, and 15-lipoxygenase (15-LO) has been implicated in the process. To address this issue, we generated transgenic rabbits that expressed 15-LO in a macrophage-specific manner and studied their susceptibility to atherosclerosis development when they were fed a high-fat, high-cholesterol (HFHC) diet (Teklad 0533 rabbit diet 7009 with 10% corn oil and 0.25% cholesterol) for 13.5 wk. Transgenic and nontransgenic rabbits developed similar degrees of hyperchol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
121
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(131 citation statements)
references
References 34 publications
8
121
2
Order By: Relevance
“…The BMT study suggests that macrophage 12/15-LO is proatherogenic in mice. This is inconsistent with previous studies by Shen et al, 17 who found that 15-LO in monocytes/macrophages is antiatherogenic in a rabbit atherosclerotic model. The conflicting conclusions from these studies may be due to differences in species (rabbit versus mouse), lipoxygenase gene products (ratio of 12HETE:15HETE), and genetic manipulation (knockout versus transgenic overexpression).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The BMT study suggests that macrophage 12/15-LO is proatherogenic in mice. This is inconsistent with previous studies by Shen et al, 17 who found that 15-LO in monocytes/macrophages is antiatherogenic in a rabbit atherosclerotic model. The conflicting conclusions from these studies may be due to differences in species (rabbit versus mouse), lipoxygenase gene products (ratio of 12HETE:15HETE), and genetic manipulation (knockout versus transgenic overexpression).…”
Section: Discussioncontrasting
confidence: 99%
“…10 -12 A variety of vascular cells are able to express 12/15-LO, including endothelial cells, 13,14 smooth muscle cells, 13,14 and monocytes/macrophages. 13,15 Overexpression of 12/15-LO in mouse endothelial cells 16 and rabbit monocytes/macrophages 17 resulted in completely opposite effects: The former was proatherogenic and the latter antiatherogenic, which indicates a possibility that different cellular expression of 12/15-LO may have different effects on atherosclerosis or that species differences may exist.…”
mentioning
confidence: 99%
“…Importantly, this enzyme displays additional properties, including the oxidation of low-density lipoproteins (10), allowing it to contribute to vascular inflammation and development of atherosclerosis (11)(12)(13)(14). Hence, and despite the potential anti-inflammatory action of 12/15-LO, animal models studying the role of 12/15-LO in the pathogenesis of atherosclerosis delivered conflicting results (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…15SHETE can serve as a substrate for 5-LO to generate anti-inflammatory lipoxins, [41][42][43] and can also serve as a ligand for the nuclear hormone receptor PPAR␥. 44,45 Two studies in transgenic rabbits that overexpressed human 15-LO indicated that 15-LO expression reduced atherosclerosis development, 46,47 whereas 2 other studies indicated that treatment of rabbits with 15-LO inhibitors reduced atherosclerosis progression. 48,49 Although murine 12/15LO has been shown to mediate atherosclerosis development in mouse models of atherosclerosis, the exact mechanisms through which this occurs are unclear.…”
Section: Discussionmentioning
confidence: 99%